Studies on the Coumarin Anticoagulant Drugs : A Comparison of the Pharmacodynamics of Dicumarol and Warfarin in Man - O’Reilly, Robert A.; Aggeler, Paul M.; Leong, Lois S. (Thrombosis and Haemostasis, 1964)
The pharmacodynamic and prothrombinopénie effects of the coumarin anticoagulant drugs warfarin and dicumarol were compared in man by means of specific chemical assays for the drugs and the Quick prothrombin time for the response. The absorption of warfarin was rapid and complete, and the prothrombinopénie response was similar after administration by any route. Absorption of dicumarol as a solution or powder was rapid while as whole tablets it was often slow. Dicumarol in solution taken orally produced higher maximum concentrations of drug in plasma, more rapid absorption rates, less unchanged drug in stool and an earlier and greater prothrombin complex response than the tablets. Only a slight effect was produced by varying the formulation of warfarin. In all subjects 15 to 30% of the oral dose of dicumarol was recovered as unchanged drug in the stool. Unchanged warfarin was not recovered from the stool in any experiment.The apparent volume of distribution (Vd) for warfarin and high doses of dicumarol was about 12.5% of body weight, approximately the size of the albumin space. The long half-time of disappearance (t½) of both drugs, their prolonged duration of action, small volume of distribution, and lack of excretion of unchanged drug in the urine are probably related to their high degree of binding to plasma proteins. The t½ and Vd for warfarin are independent of dose size; the unusual dependency of these parameters on dose size with dicumarol suggests tissue uptake, perhaps by the reticuloendothelial system.A good correlation was found between the t½ of warfarin and dicumarol and the magnitude and duration of response. Up to a certain point increasing the dose of these drugs hastened the occurrence of hypoprothrombinemia ; beyond a dose size characteristic for each individual no further hastening could be obtained.A substance extracted from the stool of subjects receiving dicumarol intravenously and orally is probably a metabolite of the drug.